Financial systems, regulatory quality, and economic growth - Lee, Chien-Chiang; Olasehinde-Williams, Godwin; Olanipekun, Ifedolapo (Routledge Journals, Taylor & Francis Ltd, 2021)
This study examined symmetric and asymmetric causal relationships among financial systems, regulatory quality, and economic performance in selected African countries. The patterns of causality and impulse responses were found to vary across the selected countries, and the following were confirmed: symmetric demand-following, symmetric supply-leading, symmetric feedback, and neutrality hypotheses. Also confirmed were negative and positive demand-following hypotheses, negative and positive supply-leading hypotheses, and negative and positive feedback hypotheses. Overall, our recommendation is that in cases where supply-leading hypothesis is confirmed, policy target should be financial development so as to either stimulate economic growth or prevent economic decline, whereas in cases where demand-following hypothesis is confirmed, emphasis should be placed on growth-enhancing policies in order to either achieve financial development or prevent crisis in the financial system. We also argue that the quality of regulation plays an important role in the finance-growth nexus as it has a mediating effect on both the real and financial sectors. We further argue that it is important to consider asymmetric dynamics when testing causality in finance-growth relationships. It is possible that the economy (financial system) would react differently to changes in financial system (economy), depending on whether the changes are positive or negative.
Keywords: Economic growth; asymmetric causality; supply-leading hypothesis; demand-following hypothesis; regulatory quality; African countries